GAPT regulates cholinergic dysfunction and oxidative stress in the brains of learning and memory impairment mice induced by scopolamine. Issue 5 (15th March 2020) - Liu, Zhenhong; Qin, Gaofeng; Mana, Lulu; Dong, Yunfang; Huang, Shuaiyang; Wang, Yahan; Wu, Yiqiong; Shi, Jing; Tian, Jinzhou; Wang, Pengwen
Abstract: Background: Cholinergic dysfunction and oxidative stress are the crucial mechanisms of Alzheimer's disease (AD). GAPT, also called GEPT (a combination of several active components extracted from the Chinese herbs ginseng, epimedium, polygala and tuber curcumae) or Jinsiwei, is a patented Chinese herbal compound, has been clinically widely used to improve learning and memory impairment, but whether it can play a neuroprotective role by protecting cholinergic neurons and reducing oxidative stress injury remains unclear. Methods: Male ICR mice were intraperitoneally injected with scopolamine (3 mg/kg) to establish a learning and memory disordered model. An LC‐MS method was established to study the chemical compounds and in vivo metabolites of GAPT. After scopolamine injection, a step‐down passive‐avoidance test (SDPA) and a Y maze test were used to estimate learning ability and cognitive function. In addition, ELISA detected the enzymatic activities of acetylcholinesterase (AChE), acetylcholine (ACh), choline acetyltransferase (ChAT), malondialdehyde (MDA), glutathione peroxidase (GPX), and total superoxide dismutase (T‐SOD). The protein expressions of AChE, ChAT, SOD1, and GPX1 were observed by western blot, and the distribution of ChAT, SOD1, and GPX1 was observed by immunohistochemical staining. Results: After one‐half or 1 month of intragastric administration, GAPT can ameliorate scopolamine‐induced behavioral changes in learning and memory impaired mice. It can also decrease the activity of MDA and protein expression level of AChE, increase the activity of Ach, and increase activity and protein expression level of ChAT, SOD, and GPX in scopolamine‐treated mice. After one and a half month of intragastric administration of GAPT, echinacoside, salvianolic acid A, ginsenoside Rb1, ginsenoside Rg2, pachymic acid, and beta asarone could be absorbed into mice blood and pass through BBB. Conclusions: GAPT can improve the learning and memory ability of scopolamine‐induced mice, and its mechanism may be related to protecting cholinergic neurons and reducing oxidative stress injury. Abstract : GAPT can improve the learning and memory ability of scopolamine‐induced mice, and its mechanism may be related to protecting cholinergic neurons and reducing oxidative stress injury.